(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Orhan Pamuk’s Snow, published in 2002 is an openly political novel that encapsulates the fragmented state of Turkey and its people. Mustafa Kemal’s efforts of modernization, officially severed all of Turkey’s ties from its Ottoman past and by doing so opposed the plurality of cultural identity. So many changes were forced to be adapted by the people of Turkey in order to establish a national identity. The sole objective of these measures was for Turkey to be accepted into the European Trade Union. Pamuk, the 2006 awardee of the prestigious Nobel Prize in literature, demonstrates the struggles of people living in an in-between country in his works. Turkish identity forms an indelible part in his oeuvre. Snow captures Turkey’s cultural, religious and political conflict, and in doing so, problematizes the question of identity. Employing the theories of Bhabha and Hall, this paper ventures to study the portrayal of Turkish identity in Pamuk’s Snow.